Evaluation of the dopamine and serotonin receptor binding activity of selected aporphines / Vani A/P Munusamy - Vani, Munusamy (2012)
Alteration in dopaminergic and serotonergic neurotransmission influences various neurological and mental disorders such as depression, anxiety, bipolar disorder, schizophrenia and drug abuse. The naturally occurring aporphine alkaloids are well known for their activity at D1, D2 and 5-HT1A receptors, but only a few have been shown to bind to the 5-HT2A receptor. Aim of this study was to identify aporphines with significant activity at dopamine and serotonin receptors using both in silico and in vitro screening approaches. A 3D homology model of the rat 5-HT2A receptor was generated using the crystal structure of the human β2-adrenergic receptor (PDB ID: 2RH1) and validated with standard 5-HT2A receptor ligands. A filtered set of aporphines obtained from the ZINC database using (S)-boldine as the backbone structure was docked into the generated 5-HT2A receptor model. A set of 13 compounds were identified with higher or comparable activity to (S)-boldine for experimental testing across the D1, D2, 5-HT1A and 5-HT2A receptors using a medium throughput radioligand receptor binding assay. (R)-roemerine was found to have selective 5-HT2A binding affinity with 20–400-fold higher affinity for the 5-HT2A receptor versus the D1, D2, and 5-HT1A receptors. Investigation into the structures of the selected compounds revealed that substitution at positions 1 and 2, particularly with a methylenedioxy group, non-substitution at positions 10 and 11 and a protonated amino group at position 6 may be responsible for the good affinity-selectivity profile of (R)-roemerine for the 5-HT2A receptor compared to the other compounds. Further analysis of the binding modes of the selected compounds also showed that the combination of an electrostatic interaction and the hydrogen bonding between the protonated amino group of (R)-roemerine and Asp155 and a pi-cation interaction with Phe339 appears to explain its enhanced affinity and selectivity as compared to the other compounds. The results illustrate the usefulness of a iii combined in silico and in vitro approach in the search for lead molecules for the development of new selective drugs acting at dopamine and serotonin receptors.